Pengaruh Kombinasi Antara Senam Aerobic Low Impact Dengan Diaphragma Breathing Exercise Pada Tingkat Keseimbangan Dinamis Lansia Di Komunitas Lansia Malang. - Hadi, Nabila Sabrina; Yuliadarwati, Nungki Marlian; Rosidah, Nikmatur (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
As individuals age, there is a gradual decline in the neurological, musculoskeletal, and endocrine systems, resulting in body imbalance and increased risk of falls. Elastic tissues, such as the lungs, decline during the aging process. The elderly usually show a decrease in physical activity due to the prevalence of pain and fatigue, leading to the perception of laziness. The approach to motivate the elderly to engage in physical activity is through low impact aerobic exercise and diaphragma breathing exercise. The aim of this research was to investigate how the combination of aerobic low impact and diaphragma breathing exercises influences the dynamic balance of older adults. The method used was one group posttest and pretest desing. The population of this study was the Berlian community, Griya Kasih and LKS - LU Pangesti, as many as 35 elderly participated in this study. Dynamic balance was assessed through the time up and go test (TUG) and evaluated using the Wilcoxon Sign Rank Test. The integration of low impact aerobic exercise with diaphragma breathing exercises notably impacts the dynamic balance of older adults, evidenced by p=0.001 (p<0.05). This research concludes that integrating aerobic low impact with diaphragma breathing exercises influences the dynamic balance levels of older adults.